Brevi osservazioni tipologico-lessicali (ed etnolinguistiche) sul carnicobarese (Atti del Sodalizio Glottologico Milanese, 2014)
Car (or Car-Nicobarese) is the most widely spoken of the Nicobaric languages, whichbelong to the Austro-Asiatic family. Car-Nicobarese word order has been described asbasically VOS. This short article attempts to offer a description of some features ofthis language (basic syntax, the use of certain affixes, some lexical facts…) on thebasis of the Bible in Car. Some interesting translation problems are mentioned too,especially where there is no precise Car word corresponding to the Greek original. KEYWORDS: Car (or Car-Nicobarese), VOS languages, classifiers, spatial relations, translation